DEOTORISASI WACANA KUASA HABA TENGKU PASCA MODERNISASI DAYAH DI ACEH - Nasir, Mohd.; Rizal, Syamsul; Al-Khalidi, M. Wali (JURNAL TARBIYAH, 2023)
This paper discusses the de-authorization of discourse on the power of “haba teungku”(Tengku said) after dayah modernization in Aceh. Implication of modernization, the authority of the “haba teungku” has faded so it is not based on “kiban kheun teungku . This paper aims to describe the authority of haba Tengku be faded the modernization and furthermore, the described haba Tengku is analyzed with Michel Foucault’s theory. Research on dayah in Aceh reveals the strong authority of discourse on the power of haba Tengku. But so far, studies that address this theme have not paid sufficient attention of weakening of discourse authority of haba Tengku after entering school at the dayah institution. This is qualitative research which data collection through observation, interview and documentation , analyzed through Michel Foucault's theory. This article concludes that: First, changes in power relations in dayah have led changes of power space. Second, this episteme is formed through three discursive stages, namely: positivity with an agreement between teungku and government, a priori historically looking at the terms and conditions that must be carried out by dayah institution carrying out modernization and archives of the regulations must be carried out by stakeholder of dayah institution.